Post-concussive mTBI in Student Athletes: MRI Features and Machine Learning - Tamez-Peña, José; Rosella, Peter; Totterman, Saara; Schreyer, Edward; Gonzalez, Patricia; Venkataraman, Arun; Meyers, Steven P. (Frontiers in Neurology, 2022)
Purpose: To determine and characterize the radiomics features from structural MRI (MPRAGE) and Diffusion Tensor Imaging (DTI) associated with the presence of mild traumatic brain injuries on student athletes with post-concussive syndrome (PCS). Material and Methods: 122 student athletes (65M, 57F), median (IQR) age 18.8 (15 to 20) years, with a mixed level of play and sports activities, with a known history of concussion and clinical PCS, and 27 (15M, 12F), median (IQR) age 20 (19,21) years, concussion free athlete subjects were MRI imaged in a clinical MR machine. MPRAGE and DTI-FA and DTI-ADC images were used to extract radiomic features from white and grey matter regions within the entire brain (2 ROI) and the eight main lobes of the brain (16 ROI) for a total of 18 analyzed regions. Radiomic features were divided into five different data sets used to train and cross-validate five different filter-based Support Vector Machines. The top selected features of the top model were described. Furthermore, the test predictions of the top four models were ensembled into a single average prediction. The average prediction was evaluated for the association to the number of concussions and time from injury. Results: 91 PCS subjects passed inclusion criteria (91 Cases, 27 controls). The average prediction of the top four models had a sensitivity of 0.80, 95% CI: [0.71, 0.88] and specificity of 0.74 95%CI [0.54,0.89] for distinguishing subjects from controls. The white matter features were strongly associated with mTBI, while the whole-brain analysis of gray matter showed the worst association. The predictive index was significantly associated with the number of concussions (p<0.0001) and associated with the time from injury (p<0.01) Conclusion: MRI Radiomic features are associated with the history of mTBI and they were successfully used to build a predictive machine learning model for mTBI for subjects with PCS that was associated with the history of concussions.